"Her Soul Beneath the Bone" On coping with breast cancer - Jacoby, Rebecca (Canadian Journal of Counselling and Psychotherapy, 2007)
This article focuses on coping with breast cancer. Several common approaches to coping are briefly discussed. Following this is a description of the process of women coping with breast cancer as it is expressed in their own poems. Qualitative analysis was conducted on eight poems. Four themes emerged from the written material: spirituality in response to corporeality; transcendence as a response to pain; giving as a response to intrusion/penetration and rehabilitation in response to destruction. The discussion focuses on coping with the threat of death as it emerged from the themes, manifested primarily in an attempt to separate from the physical and the inevitable and to unite with the spiritual and the eternal. The results of this analysis open new avenues for counsellors who work with women suffering from breast cancer.